EXPECTATIONS AND UNCERTAINTY AND THEIR RELATIONSHIPS WITH MENTAL HEALTH INDICATORS IN ADOLESCENTS OF METROPOLITAN LIMA - MATOS-RAMÍREZ, Patricia (2024)
The objective of this research was to identify how the levels of expectations and uncertainty are presented, and their relationship with mental health indicators, among high school students of Lima and Callao; for this purpose, a descriptive and correlational work was developed with high school students from educational institutions in Lima and Callao, achieving a total sample of 951;as data collection instruments we used an Expectations scale, an Uncertainty scale and the indicators of stress, anxiety, and depression from the Behavioral Disadjustment Inventory Psychosocial (INDACPS, 2021). The descriptive study managed to identify a high level for the expectations scale and a moderate level for the uncertainty, stress, anxiety and stress scales.On the other hand, the correlations were evaluated using the correlation coefficient of Spearman, finding a significant and inverse relationship in a low degree between the expectations scale with the levels of stress, anxiety and depression and with the scale of uncertainty, correlated in a high level with the scales of stress, anxiety and Depression, largely corroborating the proposed hypotheses.